Dual tasking reduces gait asymmetry of trajectory deviation during obstacle circumvention in people with Parkinson's disease - Corradini, Julia R. [UNESP]; Silveira-Ciola, Aline P. [UNESP]; Pereira, Vinicius A.I. [UNESP]; Kuroda, Marina H. [UNESP]; Faria, Murilo H. [UNESP]; Simieli, Lucas [UNESP]; Tavares, João Manuel R.S.; Barbieri, Fabio A. [UNESP] (Elsevier, 2022)
Background: Certain aspects of gait may depend on cognition, and the effects of dual-tasking (DT) on gait asymmetry (GA) during obstacle circumvention in people with Parkinson's disease (pwPD) may be walking phase-dependent. While the approaching phase requires allocating significant cognitive resources to perform the task, outweighing the available resources may increase GA. During the avoiding phase, the obstacle could be used as an external cue, enhancing the attention to the obstacle and, consequently, improving gait control and regulating GA. Objective: The study investigated the effects of obstacle circumvention during gait with DT on GA in pwPD, considering the circumvention phase. Methods: Thirty participants, 15 pwPD and 15 neurologically healthy individuals, circumvented an obstacle 20 times (in total) according to side (right and left side) and DT (presence and absence). Spatial-temporal stride parameters, medial-lateral and horizontal trajectory deviations from the original path, strategy to obstacle circumvention (lead limb away from or close to the obstacle during the crossing step), and gaze parameters were calculated during the approaching and avoiding phases. The parameters were grouped considering the side that the obstacle was circumvented during each task, and the symmetry index was calculated. Results: The results showed greater asymmetry of time of fixations, width, duration, and velocity during the approaching phase (p < 0.02), whereas the avoiding phase decreased asymmetry of medial-lateral and horizontal trajectory deviations parameters (p < 0.001) during obstacle circumvention with DT, in both pwPD and control group. Conclusions: The findings offer a basis for considering that goal-directed movement control may regulate GA in pwPD.
Keywords: Asymmetry; Cognition; Dual-task; Gait; Human movement; Parkinson's disease